El aprendizaje dialógico como "experto" en resolución de conflictos - Julio Vargas; Ramón Flecha (Universidad de La Rioja, 2013)
In this article, dialogical learning is presented as an expertise in the conflict ressolution within the educational field. Parting from the real experience of the Learning Communities project it is demonstrated that in order to be success it is necessary to involve the whole community. When students perceive that people care about their education, when they feel attended, they learn and they develop grassroots solidarity among them which protect and avoid any conflictivity. Interactive groups, which is a concrete from in which dialogical learning takes place, is a way to promote this solidarity.